2022
DOI: 10.1007/s13201-022-01588-5
|View full text |Cite
|
Sign up to set email alerts
|

Removal of of toxic metal ions (Ni2+ and Cd2+) from wastewater by using TOPO decorated iron oxide nanoparticles

Abstract: In real engineering applications, nanoparticles can face hurdles of complex behavior of pollutants, for which electrostatic forces and background electrolyte can prove to be one of the robust mechanisms to remove pollutants from wastewater. In the present work, magnetite (Fe3O4) nanoparticles (NPs) and trioctyl phosphine oxide (TOPO) coated Fe3O4 NPs were synthesized and characterized for removing divalent Ni2+ and Cd2+ ions. Morphological and chemical analysis of both NPs was performed, and batch adsorption e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“… Duan et al (2020) revealed that CuO/GO showed the highest value of the dye adsorption efficiency of 2.83 mg/g and suggested that experimental results were fitted best with pseudo-second-order model with R 2 = 0.99. Sosun et al (2022) studied that the best adsorption isotherm kinetic for the Ni 2+ and Cd 2+ ion removal was in favor of fitting of the pseudo-second-order model due to the best R 2 values obtained. They observed the maximum R 2 value of 0.98 for iron oxide nanoparticles (AgO-NP) for the removal of Ni 2+ and Cd 2+ ions in the case of pseudo-second-order model.…”
Section: Resultsmentioning
confidence: 99%
“… Duan et al (2020) revealed that CuO/GO showed the highest value of the dye adsorption efficiency of 2.83 mg/g and suggested that experimental results were fitted best with pseudo-second-order model with R 2 = 0.99. Sosun et al (2022) studied that the best adsorption isotherm kinetic for the Ni 2+ and Cd 2+ ion removal was in favor of fitting of the pseudo-second-order model due to the best R 2 values obtained. They observed the maximum R 2 value of 0.98 for iron oxide nanoparticles (AgO-NP) for the removal of Ni 2+ and Cd 2+ ions in the case of pseudo-second-order model.…”
Section: Resultsmentioning
confidence: 99%
“…pH of the medium [24,25] affects both the chemical composition of the solution and the efficiency of the treatment process [26,27]. An equally important parameter for metal extraction from solution is also the dosage of the material under study [28][29][30].…”
mentioning
confidence: 99%